Anthranil: An Aminating Reagent Leading to Bifunctionality for Both C(sp3)−H and C(sp2)−H under Rhodium(III) Catalysis. Issue 30 (28th April 2016) - Yu, Songjie; Tang, Guodong; Li, Yingzi; Zhou, Xukai; Lan, Yu; Li, Xingwei
Abstract: Previous direct C−H nitrogenation suffered from simple amidation/amination with limited atom‐economy and is mostly limited to C(sp 2 )−H substrates. In this work, anthranil was designed as a novel bifunctional aminating reagent for both C(sp 2 )−H and C(sp 3 )−H bonds under rhodium(III) catalysis, thus affording a nucleophilic aniline tethered to an electrophilic carbonyl. A tridendate rhodium(III) complex has been isolated as the resting state of the catalyst, and DFT studies established the intermediacy of a nitrene species. Abstract : Double agent : Anthranil was designed as a novel bifunctional aminating reagent for both C(sp 2 )−H and C(sp 3 )−H bonds under rhodium(III) catalysis, thus affording a nucleophilic aniline tethered to an electrophilic carbonyl. A tridendate rhodium(III) complex was isolated as the resting state of the catalyst, and DFT studies established the intermediacy of a nitrene species.